Evaluasi Standar Pelayanan Minimum dan Tingkat Kepuasan Penumpang terhadap Fasilitas Pelayanan di Terminal Kepuhsari Kabupaten Jombang - Adam Niestera Mahajana; Nugroho Utomo; fithri estikhamah (Jurnal Talenta Sipil, 2026)
Kepuhsari Terminal in Jombang Regency plays a strategic role as a Type B passenger terminal serving Rural Transportation, Inter-City Within Province (AKDP), and Inter-City Between Provinces (AKAP) services. However, the terminal's facilities and operations still exhibit several deficiencies, including inadequate waiting areas, damaged and poorly maintained sanitation facilities, limited service information, and insufficient maintenance. These conditions reduce the comfort and safety of terminal users. This study aimed to evaluate the conformity of the terminal's physical facilities with the Minimum Service Standards (MSS) stipulated in the Minister of Transportation Regulation No. PM 40 of 2015 and to analyze passenger satisfaction with the terminal services. A quantitative descriptive approach was employed. Data were collected through field observations to assess the physical condition of the terminal based on the MSS and through questionnaires administered to 100 users of Kepuhsari Terminal. The data were analyzed using Importance–Performance Analysis (IPA) to identify service attributes requiring priority improvement and the Customer Satisfaction Index (CSI) to measure overall passenger satisfaction. The IPA results showed that the average facility performance score was 2.65, while the average importance score was 3.30. The CSI value was 53.02%, which falls within the 40%–60% range and indicates a moderately satisfied level of passenger satisfaction. These findings suggest that the quality of services at Kepuhsari Terminal requires further improvement, particularly for service attributes with high importance but relatively low performance.